Examination of correlations between vitamin D and melatonin levels with sleep among women aged 18-49 years - İncedal Sonkaya, Zehra; Yazgan, Burak; Kurtgöz, Aslı; Demir, Aslıhan Dilara; İncedal Irgat, Serap (Central European Journal of Public Health, 2023)
OBJECTIVES: Although clinical research is still going on to determine any relationship between vitamin D and sleep regulation, only few studies have identified the role of vitamin D metabolism in sleep disorders. The current study aims to examine the incidence of vitamin D deficiency/insufficiency in the sample group and its effects on sleep quality and melatonin level. METHODS: A cross-sectional study was designed. A total of 79 women aged 18-49 years who applied to the research and training hospital between 1 October and 30 November 2021 participated in the study. Data were collected using a socio-demographic questionnaire prepared by the authors and the Pittsburgh Sleep Quality Index (PSQI). Blood samples were taken from the participants, also, 25-OH-vitamin D3 and melatonin levels in serum samples were measured by ELISA. RESULTS: The participants (n = 79) were aged 29.61 ± 11.14 years. The mean total PSQI scores of the participants were calculated as 5.77 ± 2.70. We determined that 64.6% of the participants had vitamin D deficiency, 21.5% had vitamin D insufficiency, and 13.9% of the participants were vitamin D sufficient. The mean melatonin level was found to be 24.77 ± 27.77 ng/L. We determined that an increase in the melatonin levels decreases the risk of vitamin D deficiency. Besides, our findings showed a good positive correlation between serum melatonin and 25 OH vitamin D3 levels (r = 0.544, p < 0.001). CONCLUSION: Our results indicate that the correction of vitamin D insufficiency can positively affect melatonin levels, therefore, it may positively contribute to the treatment of sleep disorders related to melatonin deficiency.
Keywords: ženské pohlaví; Female; Cross-Sectional Studies; Sleep Wake Disorders; vitamin D; Vitamin D Deficiency; lidé; spánek; nedostatek vitaminu D; Sleep; cholekalciferol; poruchy spánku a bdění; melatonin; Humans; Cholecalciferol; Melatonin; Vitamin D; průřezové studie